ANÁLISIS ESTRUCTURAL DEL Y2 BaCu05 TRATADO TÉRMICAMENTE - Llosa D., Melchor (2004)
It is known the YBa2Cu30H (Yl23) prepared by the solid reaction method coexists with a green phase Y2BaCu05 (Y211). In this work we study the behavior of the Y211 (pure) overheated at 11 00°C and 1300°C respectively. The starting sample was prepared by the conventional solid reaction method using appropriate amounts of Y203, BaC03 and CuO; the initial sample was green in color. From the X ray diffractogram (XRD) and using the Rietveld refinement we found that the crystalline structure is orthorhombic and belong to the Pnma spatial group. This is the sorne structure as the one found by Michael and Raveau 1 • The starting sample was overheated at 11 00°C under oxygen pressure of 0.1 atm. According with the XRD, there are no significant variations on its structure. Nevertheless after an overheating of 1300°C in the same oxygen pressure, a new phase Y203 with a cubic symmetry together with the original orthorhombic phase is observed by X-ray measurement. In this case, sorne other impurity phases, which could not be indexed in terms of any phase thus far reported in the Y-Ba-Cu-0 system, were detected as minor phases. A morphologic and chemical analysis using a scanning electronic microscope is added.